(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2016)
Peruvian export structure has been based over the years, on traditional products whose nature can be explained from Peru’s pattern of comparative advantages. In order to intensify trade flows to a greater number of markets, Peru has signed many trade agreements and, following the strategy, has concluded negotiations of the Trans-Pacific Partnership Agreement (TPP). However, Peru’s market shares in imports from countries with which it has trade agreements are low, reflecting a poor level of exploitation of treaties. The objective of this article is to identify the Peruvian potential commercial opportunities within the framework of the TPP through the use of commercial indexes such as the index of comparative advantages and the classification of strategies according to the quadrants proposed by the Ansoff matrix. The identification of commercial opportunities is the first step that needs to be taken so that Peru can take advantage of its comparative advantages and the current trade agreements by designing commercial strategies that allows our entrepreneurs and producers to be more competitive abroad.